Pengembangan Perangkat Pembelajaran Berbasis Kerangka Kerja ELPSA Menggunakan Permainan Lego - Anggraini; Purwasi, Lucy Asri; Yanto, Yufitri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The aim of the research is to develop mathematics learning tools based on the ELPSA framework using Lego games on the subject of blocks and cubes for class VIII SMP Negeri 11 Lubuklinggau City. The research subjects consisted of 9 class VIII students at SMP Negeri 11 Lubuklinggau consisting of high, medium and low students. This research is a type of development research using a 4-D model. Data collection techniques using observation, interviews and questionnaires. The questionnaires given were in the form of validity questionnaires for language experts, materials and media, as well as student and teacher practicality questionnaires. Furthermore, the average validity of the RPP and LKS learning tools is 3.99 and 4.14 with valid criteria. Furthermore, the average practicality result at the one to one trial stage was 3.04 practical criteria. Furthermore, limited trials of learning devices on students and teachers with an average of 3.09 and 3.53 with practical and very practical criteria for learning devices.